2006
DOI: 10.1002/hep.21222
|View full text |Cite
|
Sign up to set email alerts
|

An MLCK-dependent window in late G1 controls S phase entry of proliferating rodent hepatocytes via ERK-p70S6K pathway

Abstract: We show that MLCK (myosin light chain kinase) plays a key role in cell cycle progression of hepatocytes: either chemical inhibitor ML7 or RNA interference led to blockade of cyclin D1 expression and DNA replication, providing evidence that MLCK regulated S phase entry. Conversely, inhibition of RhoK by specific inhibitor Y27632 or RhoK dominant-negative vector did not influence progression in late G1 and S phase entry. Inhibition of either MLCK or RhoK did not block ERK1/2 phosphorylation, whereas MLCK regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
6
15
0
Order By: Relevance
“…Furthermore, we confirmed that the PI3K pathway decreased ERCC1 basal expression by using shRNA against FRAP/mTOR, a key kinase involved in this pathway (28,29). These findings led to the conclusion that mostly ERK2 regulated the growth factor induction of ERCC1 expression in proliferating normal and tumoral hepatocytes, whereas the PI3K pathway was mainly involved in ERCC1 basal expression.…”
Section: Cancer Researchsupporting
confidence: 73%
“…Furthermore, we confirmed that the PI3K pathway decreased ERCC1 basal expression by using shRNA against FRAP/mTOR, a key kinase involved in this pathway (28,29). These findings led to the conclusion that mostly ERK2 regulated the growth factor induction of ERCC1 expression in proliferating normal and tumoral hepatocytes, whereas the PI3K pathway was mainly involved in ERCC1 basal expression.…”
Section: Cancer Researchsupporting
confidence: 73%
“…The mechanism regulating cyclin D1 expression could be mainly ERK2/ p70S6K dependent in rat hepatocytes, showing molecular cross-talk between the MEK/ERK and Pi3K pathways. 33 In the absence of growth factors, cyclin D1 overexpression results in hepatocyte DNA synthesis and leads to activation of downstream biochemical events, including cyclin A-and E-associated kinases activation and Cdk1 induction. 34 Furthermore, an exogenous expression of cyclin D1 restored DNA synthesis in MEK-inhibited cells, suggesting that the major role for MEK in hepatocyte cell cycle progression is to increase cyclin D1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Specific deletion of p70S6K in the mouse liver blocks hepatocyte proliferation after PH due to a failure to induce cyclin E expression. 42 Our finding that p70S6K activation was delayed in Cdc42LK livers after PH confirms that p70S6K is regulated by Cdc42 during hepatocyte proliferation, which might be responsible for biosynthesis of early response proteins after PH.…”
Section: Discussionmentioning
confidence: 99%